To Study the Consumer Preference Between Coca-Cola and Pepsi in Rajkot City - Chotaliya Bhavin; Pandya Bansari; Jignesh Vidani (International Journal of Educational and Life Sciences, 2024)
This study examines Rajkot consumers' preferences between Coca-Cola and Pepsi, with particular attention to variables including accessibility, frequency of use, flavour perception, packaging, branding, price sensitivity, and the influence of age groups. By means of hypothesis testing and correlation analysis, the study pinpoints the primary variables influencing brand preference in the area. Although availability and frequency of consumption differ among age groups, the results show that they have little effect on brand preference, indicating that outside variables like distribution channels and regional habits play a larger role. Age group does not significantly influence brand preference, with both Coca-Cola and Pepsi appealing to consumers across all age categories. Taste perception was found to be a differentiated variables between the two brands, but its weak resemblance with brand preference indicates that taste is not the only factor that dominates consumer decisions. In addition, packaging and branding were shown to be influential, with a strong correlation between brand image and consumer preference. Price sensitivity and special offers were found to have limited impact, reinforcing the idea that branding and emotional connections are more powerful determinants of choice. The study concludes that while availability and taste matter, factors like branding, packaging, and emotional appeal play a more crucial role in shaping consumer behaviour. The future researches may include the factors like sustainability factors and consumer preferences on health sector. This study clarifies the influence of both the brands on the consumers is competitive.